Mitigasi Risiko Tsunami Berbasis Kerentanan Wilayah dan Persebaran Shelter Evakuasi di Telukbetung Timur - Andini Salsabila; Rahmi Mulyasari; Nissa, Selvi Hoirun; Putri, Priska Adelia; Lestari, Dwi Apriyanti (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
East Telukbetung is one of the sub-districts in Bandar Lampung City with a high vulnerability to tsunamis due to the convergence of the Indo-Australian and Eurasian plates, as well as tectonic activity from Mount Krakatau and the Semangko Fault. These geological factors increase the potential for earthquakes and tsunamis in the region, as evidenced by major events in 1883 and 2018. As part of disaster mitigation efforts, tsunami evacuation routes were mapped using Geographic Information Systems (GIS) with a network analysis approach to determine the fastest routes to shelters. The study area is classified into three risk zones: very high (274.93 ha), high (153.54 ha), and safe (696.03 ha). The results identify four main evacuation routes leading to six shelters, most of which are located in mosques and prayer facilities situated in safer zones with higher elevation. Additional shelters in the form of schools were also analyzed but not designated as primary shelters due to structural limitations and functional concerns. The planned evacuation routes take into account topography, road accessibility, and shelter capacity to ensure a fast and safe evacuation process.